2013
DOI: 10.1139/cgj-2012-0406
|View full text |Cite
|
Sign up to set email alerts
|

Model for prediction of resilient modulus incorporating matric suction for recycled unbound granular materials

Abstract: This paper presents experimental results on the effect of matric suction on the resilient modulus of four recycled unbound granular materials. The recycled materials were prepared at moisture contents ranging between 70% and 90% of optimum moisture content (OMC) and tested in a repeated load triaxial test (RLTT) apparatus under various stress regimes. Soil-water characteristic curves (SWCC) were established for each material by preparing samples at various moisture contents and measuring matric suction with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Lekarp et al [6] and Azam et al [7] reported that the aggregate gradation, fine content, applied stress level, moisture content, matric suction, and density had significant effect on Mr. In the following subsections, the influence of these factors is briefed.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Lekarp et al [6] and Azam et al [7] reported that the aggregate gradation, fine content, applied stress level, moisture content, matric suction, and density had significant effect on Mr. In the following subsections, the influence of these factors is briefed.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Several studies have reported that Mr of untreated UGMs is dependent on confining pressure and deviator stresses, which increases considerably with the increase of those stresses [7,10,2,12,13,14]. Kolisoja [15] reported that Poisson's ratio of UGMs increases with increasing deviator stress and decreasing confining pressure.…”
Section: Stress Statementioning
confidence: 99%
“…Subsequent research (Azam et al, 2013c) has led to the development of a predictive model for resilient modulus for other stress conditions. …”
Section: Influence Of Suction On Engineering Behaviour Of Ugmmentioning
confidence: 99%
“…Extensive experimental investigations were conducted by several researchers during the past decade using advanced testing techniques to measure the M R -relationships and propose models for predictions (Khoury and Zaman 2004;Yang et al 2005Yang et al , 2008Liang et al 2008;Sawangsuriya et al 2009;Craciun and Lo 2010;Cary and Zapata 2011;Nowamooz et al 2011;Azam et al 2013;Ng et al 2013;Sahin et al 2013;Sivakumar et al 2013;Salour et al 2014). These studies have provided valuable information for better understanding the influence of the on the M R .…”
Section: Introductionmentioning
confidence: 99%